Efficacy of Cardiac Resynchronization Therapy in Patients with a Narrow QRS Complex. (20th March 2021) - Nakai, Toshiko; Ikeya, Yukitoshi; Mano, Hiroaki; Kogawa, Rikitake; Watanabe, Ryuta; Arai, Masaru; Aizawa, Yoshihiro; Kurokawa, Sayaka; Ohkubo, Kimie; Kitano, Daisuke; Nagashima, Koichi; Okumura, Yasuo
Abstract : Aims . In the guidelines for cardiac resynchronization therapy (CRT), there is a gap between the Japanese Circulation Society (JCS) criteria, which specify a QRS duration of ≥120 ms, and other countries, with a QRS ≥ 130 ms. The efficacy of CRT remains controversial in patients with a narrow QRS <130 ms. The aims of this study are to evaluate the response to CRT in patients with a narrow QRS and to identify predictors of mortality. Methods . We retrospectively studied 212 patients who received CRT. They were divided into narrow QRS (<130 ms) and wide QRS (≥130 ms) groups. We compared CRT response rates and investigated whether age, gender, baseline New York Heart Association (NYHA) class, ischemic etiology, atrial fibrillation, and ventricular arrhythmias are associated with response and also predictive of mortality. Results . The CRT response rate was not significantly different between the wide QRS group and the narrow QRS group (74.6% versus 77.2%, p  = 0.6876), and the response rate in the narrow QRS group was as good as that reported worldwide. NYHA class IV was shown to be a predictor of mortality (HR 9.38, 95% CI 5.35–16.3, p  < 0.0001). Conclusions . The present study demonstrated that patients with a narrow QRS complex responded well to CRT. Even with QRS <130 ms, CRT should be tried if no other effective treatment is available.